An Evaluation of the effectiveness of the authentic task on students’ learning achievement of plant anatomy concepts in surabaya state university - Susıyawatı, Enny; Ibrahım, Muslimin; Atweh, Bill; Rahayu, Yuni Sri (Journal of Turkish Science Education, 2015)
To promote the knowledge of plant anatomy which is frequently taught using traditional method, students need to be involved in authentic learning by providing them an authentic task. Therefore, the aims of this current research are to implement a certain authentic task of plant anatomy; to evaluate the effectiveness of the task on the students’ learning achievement includes their performances, knowledge mastery, and perceptions of the task; This case study research involved a single class consisted of 25 bachelor degree students as the subjects of this research. Observation, interview, and test were implemented to collect variety information during implementation of the authentic task. The findings showed that the students’ performance scores and the percentage of mastered indicators met the minimum mastery criteria, but the percentage of classical mastery was less than the criteria. It means the authentic task had positive impact only on students’ performance, but it could not help the whole students to master the topic. However, regarding to perception, both higher and lower achiever students thought the task was authentic.
Keywords: Plant Anatomy; Authentic Task; Students’ Learning Achievement